2011
DOI: 10.1177/0731684411426810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber length and fiber content on mechanical properties of banana fiber/epoxy composite

Abstract: The main factors that influence the properties of composite are fiber length and content. Hence the prediction of optimum fiber length and content becomes important, so that composite can be prepared with best mechanical properties. Experiments are carried out as per ASTM standards to find the mechanical properties namely, tensile strength and modulus, flexural strength and modulus, and impact strength. In addition to mechanical properties, water absorption capacity of the composite is also studied. Further, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 20 publications
(24 reference statements)
1
48
0
2
Order By: Relevance
“…Takagi and Ichihara [34] indicated that the increase in fiber length improved their mechanical properties. It was determined that the tensile strength and elasticity module increased with increasing reinforcement length and started to decrease after a critical value [35,36]. They interpreted this because of low fiber-matrix adhesion [37].…”
Section: Tensile Strength Resultsmentioning
confidence: 99%
“…Takagi and Ichihara [34] indicated that the increase in fiber length improved their mechanical properties. It was determined that the tensile strength and elasticity module increased with increasing reinforcement length and started to decrease after a critical value [35,36]. They interpreted this because of low fiber-matrix adhesion [37].…”
Section: Tensile Strength Resultsmentioning
confidence: 99%
“…The tensile strength increases with increasing weight percentage of fiber. If the fiber weight ratio decrease, load is not unequally transferred to fibers, which are not good bonded between matrix and fiber resulting reduces in tensile parameter [13]. Specimens with bamboo fibers reinforcement have relatively higher strength than the specimens with siwak fibers reinforcement.…”
Section: Tensile Strength Resultsmentioning
confidence: 99%
“…7,8 Many researchers in the past have developed composites using natural fibers such as bamboo, 9-11 coir, 12,13 sisal 14-17 and banana. [18][19][20][21] Hybrid composites are materials made by combining two or more different types of fibers in a common matrix and vice versa. Hybridization of two types of materials having different properties offers some advantages over the use of either of the material alone in a single matrix.…”
Section: Introductionmentioning
confidence: 99%